How Individualized Niches Arise: Defining Mechanisms of Niche Construction, Niche Choice, and Niche Conformance. (11th May 2022) - Trappes, Rose; Nematipour, Behzad; Kaiser, Marie I; Krohs, Ulrich; van Benthem, Koen J; Ernst, Ulrich R; Gadau, Jürgen; Korsten, Peter; Kurtz, Joachim; Schielzeth, Holger; Schmoll, Tim; Takola, Elina
Abstract: Organisms interact with their environments in various ways. We present a conceptual framework that distinguishes three mechanisms of organism–environment interaction. We call these NC 3 mechanisms : niche construction, in which individuals make changes to the environment; niche choice, in which individuals select an environment; and niche conformance, in which individuals adjust their phenotypes in response to the environment. Each of these individual-level mechanisms affects an individual's phenotype–environment match, its fitness, and its individualized niche, defined in terms of the environmental conditions under which the individual can survive and reproduce. Our framework identifies how individuals alter the selective regimes that they and other organisms experience. It also places clear emphasis on individual differences and construes niche construction and other processes as evolved mechanisms. The NC 3 mechanism framework therefore helps to integrate population-level and individual-level research.